DAYA SERAP SISWA SMK PANTI ASUHAN ALQI CERIA PADA PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM): Alqi Ceria Orphanage Vocational High School Students’ Absorption Capacity in Training on Financial Statements Preparation Based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) - Aulia Hidayati; Ratih Pratiwi; Eka Merdekawati (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2021)
ABSTRACTFinancial reports for SMEs are prepared based on SAK EMKM. The purpose of this study was to determine the absorption of Alqi Ceria Orphanage Vocational High School students in the Financial Report Preparation Training Based on SAK EMKM through material suitability, extrinsic motivation and mastery of material. The research method is qualitative by describing students' absorption through predetermined indicators. Data collection techniques used are observation, documentation and literature study. The suitability of the material greatly affects the absorption of students. Participants who are interested in opening a business after graduation are very enthusiastic about participating in this training. Meanwhile from extrinsic motivation, an interesting, communicative atmosphere and sufficient time can increase students' absorption in understanding the material presented. Speakers who master the material, are communicative, who present the material well and provide time for discussion to increase students' absorption of this training.Key words : Absorption Capacity, Financial report, training, SAK EMKM ABSTRAKLaporan keuangan untuk UMKM disusun berdasarkan SAK EMKM. Tujuan dari penelitian ini adalah untuk mengetahui daya serap siswa SMK Panti Asuhan Alqi Ceria pada Pelatihan Penyusunan Laporan Keuangan Berdasarkan SAK EMKM melalui penilaian kesesuaian materi, motivasi ekstrinsik dan penguasaan materi. Metode penelitian adalah kualitatif dengan mendeskripsikan daya serap siswa melalui kriteria penilaian yang sudah ditentukan. Teknik pengumpulan data yang digunakan adalah observasi, dokumentasi dan studi kepustakaan. Kesesuian materi sangat mempengaruhi daya serap siswa. Siswa yang berminat untuk membuka usaha setelah lulus sangat antusias mengikuti pelatihan ini Sedangkan dari motivasi ekstrinsik, suasana yang menarik, komunikatif dan waktu yang cukup dapat meningkatkan daya serap siswa dalam memahami materi yang disampaikan. Pembicara yang menguasai materi, komunikatif, yang mempresentasikan materi dengan baik dan memberikan waktu untuk berdiskusi membuat daya serap siswa terhadap pelatihan ini meningkat.Kata kunci : daya serap, laporan keuangan, pelatihan, SAK EMKM.